Characteristics and controlling factors of the Triassic Xu5 tight sandstone reservoirs, Western Sichuan depression, China - Wang, Xiaojuan; Wang, Zhihong; Li, Lan; Ma, Hualing; Sun, Zhiyun; Li, Shun; Zhang, Aobo; Wang, Xuli; Yang, Ke (Frontiers in Earth Science, 2025)
The fifth member of the Xujiahe Formation in the West Sichuan depression of the Sichuan Basin has developed high-quality source rocks and large-scale delta distributary channel sediments, which have good potential for hydrocarbon accumulation, but the reservoir characteristics and genesis remain unclear. Based on the cast thin section, cathodoluminescence, X-ray diffraction, scanning electron microscope, and porosity and permeability data, the characteristics and controlling factors of physical properties of the tight sandstone reservoir in the fifth member of the Xujiahe Member were analyzed. The results show that the sandstone in the fifth member of the Xujiahe Formation is mainly being feldspar lithic sandstone and lithic sandstone, with the reservoir space type mainly lithic intragranular dissolution pores. The average porosity and permeability of the reservoir are 2.03% and 0.22 Md, respectively, making it an ultra-low porosity and extra-low permeability reservoir. The reservoir has undergone strong compaction and calcite and clay cementation. The provenance controlled the initial mineral composition of the reservoir, resulting in high rock fragment content and low quartz content in the northwest area. This led to the physical properties of sandstones in the northwest area being generally worse than those in the southwest source area. The sandstone in the delta front underwater distributary channel has low carbonate cements and matrix content, resulting in relatively good reservoir physical properties. Overall, the lithic intragranular dissolution pores and microfractures are the key factors in improving the physical properties of reservoirs.